Understanding Status of Higher Education in India: Challenges and Scepticism towards Serious Investments in the Sector - Kumar, Rahul V (Nitte Management Review, 2014)
In 2010, India had approximately 234 million people in the age group 15-24 years. This number is expected to rise by more than 10 per cent in 2020. It roughly reflects the potential demand for higher education. Given the pace of this expansion in population, there is currently a dearth of higher educational institutions in India. State funding to overcome this requirement has not been a successful model. Private higher educational institutions have attempted to fill this gap. However, in many of the federal states private investment in higher education face hurdles. There are also a few federal states where there is a proliferation of private higher educational institutions. Lack of effective guidelines, and inefficient regulatory and accreditation practices resulted in poor quality of majority of these institutions. The paper examines the higher education scenario in India and attempts to point out why very few serious investors invest in higher educational sector. Several factors are responsible for this. Primary among these factors is the legal and legislative hurdles in several federal states. It is also seen that the bad precedent set by the existing institutions also dissuade serious investments. These factors have led to specific problems which face any serious investor in this sector in India. The paper identifies these problems and suggests that a possible change in perception towards higher education would be most desired in the current milieu. Certain contours of these change in perception are identified.